2001
DOI: 10.1007/pl00000805
|View full text |Cite
|
Sign up to set email alerts
|

Signalling roles of mammalian phospholipase D1 and D2

Abstract: Phospholipase D (PLD) catalyses the hydrolysis of phosphatidylcholine to generate the lipid second messenger, phosphatidate (PA) and choline. PLD activity in mammalian cells is low and is transiently stimulated upon activation by G-protein-coupled and receptor tyrosine kinase cell surface receptors. Two mammalian PLD enzymes (PLD1 and PLD2) have been cloned and their intracellular regulators identified as ARF and Rho proteins, protein kinase Calpha as well as the lipid, phosphatidylinositol bisphosphate (PIP2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
134
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(141 citation statements)
references
References 118 publications
3
134
1
1
Order By: Relevance
“…The result suggests that PLD activation by WKYMVM is essential for the phagocytic activity in the DCs. Since PA generation is the primary consequence of PLD activation (Lennartz, 1999;Cockcroft, 2001), investigation on the effect of the exogenous addition of PA on the phagocytic activity of DC2.4 cells was carried out. The phagocytic activity in the DC2.4 cells was indeed enhanced by the exogenously added PA (Figure 7B), supporting the hypothesis that PLD activation is necessary for the phagocytic activity in DC2.4 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The result suggests that PLD activation by WKYMVM is essential for the phagocytic activity in the DCs. Since PA generation is the primary consequence of PLD activation (Lennartz, 1999;Cockcroft, 2001), investigation on the effect of the exogenous addition of PA on the phagocytic activity of DC2.4 cells was carried out. The phagocytic activity in the DC2.4 cells was indeed enhanced by the exogenously added PA (Figure 7B), supporting the hypothesis that PLD activation is necessary for the phagocytic activity in DC2.4 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the regulation of this isoform, but it does not appear to be affected by small monomeric GTPases. In the absence of further evidence, some workers have suggested that the purified activity may have been related to PLD2 (40). Two related polyphosphoinositolactivated PLD isoforms have been cloned on the basis of yeast PLD sequences (262,266) and are known as PLD1 (120 kDa) (81, 82, 122, 187) and PLD2 (106 kDa) (43,130).…”
Section: Substrates For Lppmentioning
confidence: 99%
“…In the presence of PIP 2 or PIP 3 , PLD1a and PLD1b are activated by a number of small GTPases, including ADPribosylation factor (ARF) family members, Rho family members (RhoA, Rac, and Cdc42), Ral I and by PKCs, particularly PKC-␣ and PKC-␤ (61,69,81,96,113,139,140). Brefeldin A, a fungal metabolite that interferes with ARF GDP/GTP exchange, inhibits PLD1 activation and certain forms of vesicular trafficking (40,113). Interestingly, phorbol ester stimulation of PLD1 in the presence of PIP 2 or PIP 3 does not require ATP but does require the NH 2 -terminal 168 amino acids (hence known as the phorbol ester-binding domain).…”
Section: Substrates For Lppmentioning
confidence: 99%
See 1 more Smart Citation
“…Phospholipase D (PLD) catalyses the hydrolysis of phosphatidylcholine to generate phosphatidic acid (PA), a second messenger, and choline (Exton, 1998;Cockcroft, 2001). Two main products of PLD genes have been described: PLD1 and PLD2 Park et al, 1997;Lopez et al, 1998;Sung et al, 1999), as well as their regulators (Powner and Wakelam, 2002).…”
Section: Introductionmentioning
confidence: 99%